2017
DOI: 10.1177/0883073817718731
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine and Postural Orthostatic Tachycardia Syndrome: A Review of Current Literature

Abstract: The human papillomavirus (HPV) vaccine is efficacious in preventing complications of human papillomavirus infection including cervical cancer. However, there have been case reports of adverse events occurring after vaccination, one being postural orthostatic tachycardia syndrome (POTS). This article reviews published data and other available information regarding the relationship between the human papillomavirus vaccine and POTS. Background information is provided regarding the human papillomavirus vaccine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…45 Reports of these latecoming concerns largely originated from outside the mainstream medical community and were amplified among sections of the public through the Internet and social media. 46 However, evidence of serious safety problems from such reports has been decidedly lacking, consisting of temporally associated case reports with a lack of biological plausibility or only weak theoretical plausibility 45,[47][48][49] ; for example, autoimmune or autoinflammatory syndrome induced by adjuvants, as proposed, is an ill-defined constellation of general symptoms and disparate illnesses and is not a medically recognized diagnosis. 50 Conversely, public health investigations, surveillance reviews, and epidemiologic studies to date have not confirmed any link between HPV vaccination and several of these emerging safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…45 Reports of these latecoming concerns largely originated from outside the mainstream medical community and were amplified among sections of the public through the Internet and social media. 46 However, evidence of serious safety problems from such reports has been decidedly lacking, consisting of temporally associated case reports with a lack of biological plausibility or only weak theoretical plausibility 45,[47][48][49] ; for example, autoimmune or autoinflammatory syndrome induced by adjuvants, as proposed, is an ill-defined constellation of general symptoms and disparate illnesses and is not a medically recognized diagnosis. 50 Conversely, public health investigations, surveillance reviews, and epidemiologic studies to date have not confirmed any link between HPV vaccination and several of these emerging safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is often triggered by an illness, a prolonged recovery period, or an extreme athletic activity [3,5,6]. A recent review of literature examined the relationship between the human papillomavirus (HPV) vaccine and POTS, which is an association that was reported in a few case reports, and found no evidence that the HPV vaccine was a trigger for POTS [8]. This entity is important for pediatricians to recognize because early diagnosis and intervention can prevent significant functional consequences as well as reduce unnecessary investigations.…”
Section: Discussionmentioning
confidence: 99%
“…2. Overall, the number of reported or observed POTS cases after vaccination was generally lower compared to the expected incidence that would occur naturally in the target population under almost all assumptions for all regions and countries, except for Denmark, where the majority of POTS cases that have been reported come from one syncope unit (Butts et al, 2017; Pharmacovigilance Risk Assessment Committee EMA, 2004). 3.…”
Section: Dissenting Opinions Regarding Safetymentioning
confidence: 95%
“…However, the data at this time constitute only weak temporal associations between events, and their hypothesized mechanisms have not been scientifically proven. The small sample sizes, inherent selection biases, and lack of control populations preclude drawing any scientifically valid conclusions of causality (Arana et al, 2017;Butts et al, 2017;Works Health Organization, 2018).…”
Section: American Autonomic Society Positionmentioning
confidence: 99%